The scope and application of wa‘ad, muwa'adah and wa'dan in Islamic finance - Abdul Aziz Bello, Shafi'i; Hassan, Rusni (Merit Research Journal, 2013)

(untitled)
Islamic laws cover all aspects of human behaviours and govern the Muslims ways of life. It is wider than the Western understanding of law and they regulate Islamic transactions. This paper demonstrates scope and application of Wa'ad (promise), Muwa'adah and Wa'dan (two promises) in Islamic finance. Brief discussion on the definitions and legal principles of Wa‘ad, Muwa‘ada and Wa‘adanfrom perspectives of Islamic law as well as the concept of wa'ad under common law were reported in the paper. Furthermore the paper critically analyses the concept and pracrtice of wa'ad, muwa'adah and wa'dan in Islamic transaction (sale and purchase). Similarly, the concept and practice of wa'ad in Islamic banking system in Malaysia were also discussed. The application of wa'ad in islamic banking products were also explained such as the use of wa'ad for foreign exchange option, Islamic financial market and foreign exchange option for a multinational bank. The paper ended with some illustrations on the use of wa'ad for short selling in Islamic finance.